River Monitoring: In View of the Physical Habitat of the River and the Presence of Macroinvertebrates - Susy Amizera; Elvira Destiansari; Didi Jaya Santri; Zainal Arifin; Nike Anggraini (Biota, 2022)
Monitoring of river aims to determine the condition of water quality. One alternative effort that can be used to have description of water quality is by reviewing the condition of the river's physical habitat. In this regard, the physical habitat condition will affect the presence of macroinvertebrates. The aims of this study was to determine the quality of river by observing the physical habitat of the river and the presence of macroinvertebrates. Data collection techniques are carried out spatially by dividing the river into several segments by taking into the state of the environment which include industry area, agriculture (rice field) area, housing area, pipe oil area and the springhead of the river. Based on the results of the study, it shown that the condition of river waters can be categorized in an unhealthy condition. This can be seen from the type of substrate cover, river bank stability and human activities in the river. It causes by eroding, agricultural activities, livestock, waste disposal, sand mining and garbage disposal. These conditions also affect the composition of macroinvertebrates found in this waters, which have a high level of tolerance in unhealthy physical habitat conditions such as Limnodrilus sp. and Aulodrilus sp